The efficiency of using integrated control agents to manage the Dubas bug Ommatissus binotatus lybicus De Berg (Homoptera: Tropiducidae) in Karbala Governorate - Tami, Mohammad Abd Ali; Kareem, Ali A.; Ali, Muhsun Abid (Journal of Kerbala for Agricultural Sciences, 2023)
This study aims to rate the efficiency of using chemical pesticides, bio-fungicides, and the interaction between them against the nymphal and adult stages of the Dubas insect (Ommatissus binotatus lybicus De Berg). Anyhow, the laboratory and field results of the pesticides significantly affected the treated phases. The field results of the treatments were significantly increased after around two weeks, as for the average percentage of death in the treated nymphs. It reached 89.29-75.03-72.5-71, respectively. The results of the interaction treatments between fungal biocides (Beauveria bassiana, Paecilomyces sp, Beauveria bassiana, Metarhizium anisopliae, Metarhizium anisopliae, and Paecilomyces sp) were significantly increased after two weeks of treatment, as the average percentage of death of the treated nymphs reached 63.95 -77.19 -63.5, respectively. The laboratory results of the treatments were significant for the pesticides used after nine days of treatment, as the average percentage of death of the adults reached 86.01 - 39.25 -32.16 -36.81, respectively. Moreover, the interaction coefficients between the fungal biocides mentioned in the paragraph above were significant after nine days of treatment. The average percentage of treated adults' deaths reached 38.13 -39.64 37.57 - 86.02 to treat the interaction between the chemical pesticide Actara and B. bassiana. The chemical pesticide Actara excelled in the field experiment, as it gave the highest percentage of mortality when used at concentrations of 1-1.5 g/L after two weeks of treatment. The average percentage of nymphs killed was 89.29. As for the laboratory experiment results, the chemical pesticide Actara was also superior, as it gave the highest mortality rate for adult females. The average mortality rate for adult females reached 86.01 after nine days of treatment compared to the rest of the treatments using other pesticides.